Assessment of Mechanical and Tribological Properties of Al 2024- SiC - Graphene Hybrid Composites. (2017) - Kumar, H.G. Prashantha; Xavior, M. Anthony
Abstract: In the recent years, enormous research has been carried out and reported on ceramic and carbon based reinforcement. Graphene, no wonder has attracted significant research interest due to its extensive physical properties at its single atomic thickness and 2-D morphology. The current studies focus on the role of Graphene in reducing the wear and frictional coefficient of Al 2024- SiC - Graphene reinforced hybrid composites. Reinforcement chosen is 4, 8 and 12 wt. % of SiC with 0.5 wt. % of Graphene to investigate the lubricating property under dry wear conditions and processed through the ultrasonication and ball milling. The processed mixtures are hot compacted and microwave sintered. Hardness, density, X-ray diffraction and flexural strength analysis were done on developed composites. The dry frictional wear test were carried out using pin-on-disc tribometer to evaluate the effect of Graphene and SiC content in the composite under various normal load and disc speed conditions. Further, wear resistance and a reduction in the coefficient of friction (μ) values compared to pure alloys were observed. Surface roughness values (Ra) and microscopic studies on wear tracks were carried out. The possible tribological potential coupled with improved mechanical properties and surface roughness of Al 2024- SiC - Graphene hybrid composite processed through powder metallurgy were discussed.